Workplace environment and job performance of police officer during the COVID-19 crisis / Muhammad Zulhelmi Zakarani and Nurul Hidayana Mohd Noor - Zakarani, Muhammad Zulhelmi; Mohd Noor, Nurul Hidayana (Universiti Teknologi MARA, 2021)
The objective of this study is to investigate the influence of the workplace environment that is physical environment, supervisor support, and performance feedback on the performance of employees at the Sepang Police District Headquarters. This study has adopted a cross-sectional online-based survey design. The final data of 100 police officers are first analyzed using Pearson correlation. Then, regression analysis was used to develop predictive models of job performance. The results indicated that the physical environment, supervisor support, and performance feedback significantly influence the performance of employees. Supervisor support also acts as the most significant predictor of job performance. The overall results from this research are expected to make a contribution to the current literature regarding the roles of the workplace environment in influencing employee job performance during the COVID-19 crisis. From the managerial perspective, the results of this research provide crucial insights for the management regarding the policy that might increase job performance.